Misreporting of energy intake in severely obese pregnant women in Scotland, UK - Mohd Shukri, Nor Azwani; Bolton, Jennifer L.; Norman, Jane E.; Walker, Brian R.; Reynolds, Rebecca M. (Dietitians Association of Australia, 2012)
Under-reporting of self-reported energy intake (EI) has been described in female, overweight, and pregnant subjects but little is known about its prevalence in severely obese pregnancy. This study aimed to assess this in severely obese pregnant women (body mass index ≥40 kg/m2 ) who completed a food frequency questionnaire at 28 weeks gestation for a cohort study of severe obesity in pregnancy, and to compare it to the prevalence in normal-weight pregnant women. Estimated energy requirement (EER) was calculated using Dietary Reference Intakes equations (Institute of Medicine, 2002) with adjustment for pregnancy requirements. EI : EER ratio was used to categorize each person as under-, adequate or over-reporter by using published cut off-points (Nowicki et al., 2011). 98 obese and 68 lean pregnant women were included. Median EI : EER ratio was lower in obese than in lean (0.72 vs 0.95, p < 0.001), indicating higher prevalence of under-reporting in obese as compared to in lean (49.0% vs 14.7%). Over-reporting was lower in obese (7.1%) than in lean (13.2%).In both groups, underreporters reported lower intakes of fats, dietary cholesterol and sugars but higher of dietary fi bre, vitamin C, iron, calcium and folic acid (all p < 0.05), compared to adequate or over-reporters. In conclusion, there is a higher prevalence of energy under-reporting in obese, compared to in lean pregnant women in this study. Statistical adjustment of energy on nutrient intakes may reduce (but not fully remove) the infl uence of energy misreporting. Data should still be interpreted with caution, particularly in identifying dietary insufficiency.